Multibeam bathymetry processed data (EM 120 echosounder entire dataset) of RV SONNE during cruise SO175 - Stefanie Gaide; Paul Wintersteller (PANGAEA, 2020)
Swath sonar bathymetry data used for that dataset was recorded during RV SONNE cruise SO175 using Kongsberg EM 120 multibeam echosounder. The cruise took place between 12.11.2003 and 30.12.2003 in the Gulf of Cadiz. The expedition aimed at a better understanding of the interaction between dynamic processes in a seismically active region with slow plate convergence. Bathymetric mapping with the multibeam echosounder (MBES) SIMRAD EM120 was utilized to image the nature of the Gibraltar Arc thrust wedge, a proposed subduction zone, and to identify possible sampling sites. CI Citation: Paul Wintersteller (seafloor-imaging@marum.de) as responsible party for bathymetry raw data ingest and approval. Description of the data source: During the SO175 cruise, hull-mounted KONGSBERG EM120 multibeam ecosounder (MBES) was utilized to perform bathymetric mapping in middle to deep water depths. Two linear transducer arrays in a Mills Cross configuration transmit acoustic signals of a nominal sonar frequency of 12 kHz. With 191 beams, the emission cone has a dimension of max 140° across track and 1° along track, while the actual beam footprint is 2° by 2°. Depending on the roughness of the seafloor, the swath width on a flat bottom is maximum six times the water depth. For further information on the system, consult https://www.km.kongsberg.com/. During the cruise, an opening angle of 135 - 140° was used depending on the state of the sea, though restricting the coverage of the swath to gain a more continuous spacing of beams on the ocean floor. The spacing within these limits was controlled automatically by the echosounder system. To convert the recorded travel times into water depth, several sound velocity profiles were obtained with the shipboard CTD, providing a correction for ray bending for each beam. Responsible person during this cruise / PI: Achim Kopf (akopf@marum.de) & Ingo Grevenmeyer (igrevemeyer@geomar.de) Description of data processing: Postprocessing and products were conducted by the Seafloor-Imaging & Mapping group of MARUM/FB5, responsible person Paul Wintersteller (seafloor-imaging@marum.de). The open source software MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, https://www.mbari.org/products/research-software/mb-system, 2017) was utilized for this purpose.SVPs taken during this cruise were not sufficient enough to correct the recorded bathymetric data. Therefore sound velocity profiles were modelled using reference profiles from the world ocean atlas (S. Levitus, 1982), extracted and calculated through the MB-System program mblevitus by utilizing the DelGrosso equation. The surface sound speed has then been adapted according to the recordings during this cruise while there were no further corrections for roll, pitch and heave applied during postprocessing. A tide correction was applied, based on the Oregon State University (OSU) tidal prediction software (OTPS) that is retrievable through MB-System. CTD measurements during the cruise were sufficient to represent the changes in the sound velocity throughout the study area. Using Mbeditviz, artefacts were cleaned manually. NetCDF (GMT) grids of the edited data as well as statistics were created with mbgrid. The published bathymetric EM120 grid of the cruise SO175 has a resolution of 35 m. No total propagated uncertainty (TPU) has been calculated to gather vertical or horizontal accuracy. A higher resolution is, at least partly, achievable. The grid extended with _num represents a raster dataset with the statistical number of beams/depths taken into account to create the depth of the cell. The extended _sd -grid contains the standard deviation for each cell. The DTMs projections are given in Geographic coordinate system Lat/Lon; Geodetic Datum: WGS84. All grids produced are retrievable through the PANGAEA database (www.pangaea.de). Chief Scientist: Achim Kopf (akopf@marum.de) CR: https://elib.suub.uni-bremen.de/ip/docs/ELibD1195_228.pdf CSR: https://www2.bsh.de/aktdat/dod/fahrtergebnis/2003/20050152.htm